A Case Study on the effectiveness of Crisis Management within a Global Organisation - Noble, James (2010)
Worldwide events like the BP oil incident (2010) and subprime crisis (2007) have created surprises whereby organisations have had to quickly respond. These crises are occurring in an increasingly competitive and turbulent business arena which has made effective preparation and timely responses even more critical. Much of crisis management literature directly focuses on man-made disasters (Piotrowski, 2006:12), however this research among other limited studies provides exclusive insight into how an organisation responds to an event which is uncontrollable to prevent or contain. This study uncovers how Experian; a global organisation, prepared, responded and learned from the Chile earthquakes (2010). Incorporating a well-rounded appreciation of the crisis and organisational management behaviour enabled this research to capture a holistic account of the effectiveness of their theoretical and practical crisis management capabilities. The implementation of a number of key conceptual frameworks was used to formulate the research model to reflect contemporary organisational crisis management issues. The model consists of multiple phases of the crisis event (pre, event and post), factors (identification, preparation, prevention, containment, recovery and learning) and themes (leadership, communication and stakeholder involvement). This researcher acknowledges the interconnected nature of Experian’s risk management and business continuity activities and uses this as a foundation to form an understanding of what enables or disables them to manage the crisis.